Incidence and risk factors of embolized particles in carotid artery stenting and association with clinical outcome. (15th January 2017) - Ledwoch, Jakob; Staubach, Stephan; Segerer, Manuela; Strohm, Henning; Mudra, Harald
Abstract: Background: One of the mechanisms for periprocedural neurologic events in carotid artery stenting (CAS) is catheter manipulation within the aorta and supraaortic arteries causing plaque embolization. Therefore, the present analysis sought to determine risk factors for embolic particle dimensions and their relationship with adverse clinical events after CAS. Methods: Between 1999 and 2015 embolic protection devices (EPD) of a total of 944 CAS procedures were evaluated regarding the occurrence and size of captured particles. Results: Particles were found in 819 of 944 (87%) EPDs. Larger particles were detected in procedures using open cell stents (150 ± 282 μm vs. 107 ± 177 μm; p = 0.005) and longer stents (≥ 40 mm) (165 ± 315 μm vs. 122 ± 215 μm; p = 0.026). With increasing learning curve, particle size was continually reduced (168 ± 282 μm in the first third of the cohort vs. 127 ± 309 μm in the second third vs. 108 ± 114 μm in the last third; p = 0.009). Longer stents and use of Acculink stent were found to be independent predictors for particle diameter. In patients who died or sustained a stroke during long-term follow-up (median 5.5 years [IQR 2.6–7.9]) significantly larger particles were captured during CAS compared to those patients with an uneventful follow-up (160 ± 330 μm vs. 121 ± 195 μm; p = 0.047). Conclusions: In the vast majority of CAS procedures particles could be retrieved from the EPDs used. Procedural characteristics such as stent type and stent length were associated with larger particles.